“Surprise” and the Bayesian Brain: Implications for Psychotherapy Theory and Practice - Holmes, Jeremy; Nolte, Tobias (Frontiers in Psychology, 2019)
The free energy principle (FEP, Friston 2010) has gained widespread interest and growing acceptance as a new paradigm of brain function, but has had little impact on the theory and practice of psychotherapy. The aim of this paper is to redress this. Brains rely on Bayesian inference during which ‘bottom-up’ sensations are matched with ‘top-down’ predictions. Discrepancies result in ‘prediction error’. The brain abhors informational ‘surprise’, which is minimised by a) action enhancing the statistical likelihood of sensory samples, b) revising inferences in the light of experience, updating ‘priors’ to reality-aligned ‘posteriors’ c) optimising the complexity of our generative models of a capricious world. In all three free is converted to bound energy. In psychopathology energy either remains unbound, as in trauma and inhibition of agency, or manifests restricted, anachronistic ‘top-down’ narratives. Psychotherapy fosters client agency, linguistic and practical. Temporary uncoupling bottom-up from top-down automatism and fostering scrutinised simulations sets a number of salutary processes in train. Mentalising enriches Bayesian inference, enabling experience and feeling states to be ‘metabolised’ and assimilated. ‘Free association’ enhances more inclusive sensory sampling, while dream analysis foregrounds salient emotional themes as ‘attractors’. FEP parallels with psychoanalytic theory are outlined, including Freud’s unpublished project, Bion’s ‘contact barrier’ concept, the Fonagy/Target model of sexuality, Laplanche’s therapist as ‘enigmatic signifier’, and the role of projective identification. Therapy stimulates patients to become aware of and revise the’ priors’ they bring to interpersonal experience. In the therapeutic ‘duet for one’, the energy binding skills and non-partisan stance of the analyst help sufferers face trauma without being overwhelmed by psychic entropy. Overall, the FEP provides a sound theoretical basis for psychotherapy practice, training and research.